THEORETICAL PRINCIPLES OF IMPROVING THE MODERN CORPORATE CONTROL SYSTEM IN JOINT STOCK COMPANIES - SUYUNOV DILMUROD KHOLMURADOVICH (International journal of economic perspectives, 2022)
The article analyzes the concept of compliance control at corporate enterprises, the views of economists in this area, the principles of compliance control, implementation methods and scientifically substantiated conclusions on this matter.